INDICATION AND FREQUENCY OF IMPLANTATION OF PERMANENT PACEMAKER IN COMPLETE HEART BLOCK PATIENTS IN A TERTIARY CARE HOSPITAL IN RAWALPINDI - Tanvir Ahmad Raja; Muhammad Kashif; Adeel Ur Rehman; Azhar Kiyani; Faizania Shabbir; Tausif Ahmed Rajput (Pakistan Armed Forces Medical Journal, 2018)
Objective: To find out the indication and frequency of permanent pacemaker implantation in complete heart block patients (CHB). Study Design: Prospective cohort study. Place and Duration of Study: Rawalpindi Institute of Cardiology, Rawalpindi for a period of six months from Mar 2016 to Sep 2016. Material and Methods: Total 153 patients of both genders coming to Rawalpindi Institute of Cardiology with complete heart block were included in the study. The patients fulfilling the inclusion criteria were evaluated for the etiology of complete heart block by history, physical examination, electrocardiography, blood tests, chest x-ray and echocardiography. Later their outcome (pacemaker implantation/medical treatment/death) was determined. Results: Myocardial infarction was found out to be the cause for CHB in 32.1% patients. Out of 153 patients, 12 patients died. In the remaining 141 patients, 77 were implanted with a pacemaker. Conclusions: Myocardial infarction accounted for 32.1% cases of complete heart block and a significant number of patients were implanted with a permanent pacemaker. Hence the trend of pacemaker use is on a rise.